Analysis of Fares and Subsidy Needs for Public Transportation using The Vehicle Operating Cost Approach (Case Study: Corridor 2 Trans Cirebon) - Hariani, Mira Lestira; Darmun, Darmun; Anggraeni, Catur Wulan; Ramadhan, Fariz; Budiarto, Yanto (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2023)
Public transportation subsidies or what is called the Public Service Obligation (PSO) is an important indicator in the public transport system to ensure the sustainability of the operation of the public transportation system. Subsidies are government interventions in controlling transportation fares so that people can use public transportation at affordable fares. This study aims to provide an overview of the determination of fares and the amount of subsidy needed in corridor 2 of Trans Cirebon. Fare analysis is determined using the vehicle operating cost and Willingness To Pay (WTP) approaches which will then form the basis for providing an overview of the subsidy that should be provided by the Government in an ideal Trans Cirebon operation. This research shows that: 1) the fare currently applied are still in accordance with the WTP value the people of Cirebon City; 2) for an ideal Trans Cirebon operation, a vehicle operating cost of Rp. 6,135,159,933.29/year is required; 3) the amount of subsidy required ranges from Rp. 5,705,919,933.29/year to Rp. 6,108,879,933.29/year depending on the achievement value of the load factor and the fare applied.